Retraction Notice: Beyond Sight: Developing Inclusive Health-Related Exercise For Visually Challenged Learners - Novie Queen T. Magwate; Chiedel Joan G. Sandiego (INSPIREE: Indonesian Sport Innovation Review, 2025)
Retraction Notice The Editorial Board of INSPIREE: Indonesian Sports Innovations Reviews hereby states that the following article: Title: Beyond Sight: Developing Inclusive Health-Related Exercise For Visually Challenged LearnersAuthor(s): Novie Queen T. Magwate, Chiedel Joan G. Sandiego. has been RETRACTED due to a proven violation of the Publication Ethics Code, specifically related to multiple submission (the simultaneous submission of a manuscript to more than one journal). This practice constitutes a serious breach of scientific integrity, as it undermines transparency, validity, and the credibility of the publication process. In order to uphold academic integrity and protect the reputation of the journal, the Editorial Board has imposed the sanction of retraction on this article, and the violation will be recorded according to our established procedures. INSPIREE is fully committed to enforcing publication ethics standards, in line with the guidelines of the Committee on Publication Ethics (COPE), to ensure the quality and credibility of every article published (COPE's Retraction Guidelines) We sincerely thank our readers and the academic community for their understanding. Sincerely,The Editorial BoardINSPIREE: Indonesian Sports Innovations Reviews